Instrumen Musik Talempong Minangkabau dalam Kajian Organologis - Syeilendra Syeilendra (Fakultas Bahasa dan Seni UNP, 2009)
The purpose of this study is to make a description and a documentation of the manufacturing process from the beginning to the end. A traditional technique that has been integrated in creators’ habit is used in the manufacturing. According to the technique, the manufacturing is done in a workshop by using uncomplicated tools. The descriptive analysis method was apllied in this qualitive research. The main problem was analyzed systematically, factually, accurately, and originally through itemized thinking process of literature reviews, observation, recordings, photographies, an type predetermination, human role as a research instrumen, exploration, interview, and diary note. In the manufacturing, the black clay mixed with husk and red clay is grinded. The main materials are brass or copper (Cu), tin (Sn), and iron (Fe). The manufacturing process is begun by making a talempong lilin (waxed talempong) as a model, bandaging the talempong lilin with the mixed-clay to make a talempong tanah moulder, and foundrying the alloy. Then, the mauder is burned to extract the wax and in sequence the alloy is poured in. Finally, the moulder is destroyed and talempong is produced. After cleansing, flattening, filing, grinding, and polishing, talempong is ready to purchase. The are three kinds of talempong in size: (1) big; (2) medium; and (3) small. Talempong is fitted in a traditional way by stroking the outside part to fit up the tone or stroking the inside part to fit down the tone. Keyword: instrument music; talempong, minangkabau